2019
DOI: 10.1021/jacs.9b02286
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Site Cascade Oxygen Reduction Mechanism on SnOx/Pt–Cu–Ni for Promoting Reaction Kinetics

Abstract: Designing highly active oxygen reduction reaction (ORR) catalysts is crucial to boost the fuel cell economy. Previous research has mainly focused on Ptbased alloy catalysts in which surface Pt is the solely active site and the activity improvement was challenged by the discovered scaling relationship. Herein we report a new concept of utilizing dual active sites for the ORR and demonstrate its effectiveness by synthesizing a SnO x /Pt− Cu−Ni heterojunctioned catalyst. A maximum of 40% enhancement in the appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 40 publications
3
70
0
Order By: Relevance
“…89 Shen et al reported the design of dual adsorption sites by synthesizing SnO x /Pt-Cu-Ni composites to circumvent the scaling relation between *OOH and *OH on the same adsorption site and promote the catalytic activity ( Figure 5). 90 Theoretical studies demonstrated a dual-site cascade mechanism, in which the first two steps take place on a SnO x site (*OOH formation is a potential-determining step with the lowered barrier of 0.…”
Section: Strategies To Break the Scaling Relation In The Oxygen Reducmentioning
confidence: 99%
“…89 Shen et al reported the design of dual adsorption sites by synthesizing SnO x /Pt-Cu-Ni composites to circumvent the scaling relation between *OOH and *OH on the same adsorption site and promote the catalytic activity ( Figure 5). 90 Theoretical studies demonstrated a dual-site cascade mechanism, in which the first two steps take place on a SnO x site (*OOH formation is a potential-determining step with the lowered barrier of 0.…”
Section: Strategies To Break the Scaling Relation In The Oxygen Reducmentioning
confidence: 99%
“…Reproduced with permission. [56] Copyright 2019, American Chemical Society. f) The mechanism for the OER in acidic electrolytes: AEM and LOM.…”
Section: General Comments On Catalytic Activity Descriptorsmentioning
confidence: 99%
“…[47b,56] For instance, SnO x on PtCuNi could be an active site for the first two ORR reactions, whereas the remaining steps took place at Pt-enriched surface of PtCuNi (Figure 6d,e). [56] Figure 6d As with the ORR, the binding strength of the reaction intermediates could affect the OER activity, making band shift an essential factor to explain the catalytic performance of the transition metal and alloy catalysts. [10a] For example, incorporation of Co and Ni into Ir weakens the binding of the oxygen intermediates in the RDS, lowering the d-band center of Ir (from −3.89 to −4.09 eV).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sn 3 O 4 /SnO 2 heterostructures were used as gas sensor [3], SnO/Sn 3 O 4 heterostructures were used as photocatalyst [4]. And SnO x composites were used as active oxygen reduction reaction (ORR) catalysts to promote reaction kinetics [5]. And SnO/SnO 2 heterojunctions assembled from ultrathin nanosheets showed improved properties of gas sensors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%